Defining the effect of the making-up the two-unit trains on the basis of the single-unit destinations - Мазуренко, Олександр Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
There was researched the effect of the making-up the two-unit trains under the operative conditions onto the expenses on organization of the wagonflows into the trains on the railway direction. The criterion of the decision making concerning the making-up the two-unit trains was defined. The method of its usage was developed